2012
DOI: 10.1080/09540121.2012.672814
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and reproductive health needs of HIV-positive women in Botswana – a study of health care worker's views

Abstract: Botswana's HIV prevalence is one of the highest in the world at 31.8% in the 15-49 years antenatal population. Being HIV-positive for a woman presents unique challenges with regard to sexuality, child bearing, and partner relations. To ensure optimal sexual and reproductive health (SRH) of HIV-positive women, it is important to understand how health care workers (HCWs) are prepared to address SRH issues such as contraception, fertility desires, and partner violence. This study reports on a knowledge, attitudes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 5 publications
0
12
0
3
Order By: Relevance
“…The underlying assumption was that HIV-infected women may have worse access to or demand for contraception than HIV negative women, potentially due to barriers accessing and/or utilizing family planning services or fear of stigma from providers. [41], [42], [43] Overall, we found that approximately half of women with unintended births were actively trying to avoid pregnancy and presumably experienced contraceptive failure. Furthermore, in our adjusted model, there was no association between self-reported HIV status and contraception use, suggesting that, in Zimbabwe, the challenges to obtaining effective contraception apply equally to both HIV-uninfected and HIV-infected women, regardless of when they learned their serostatus.…”
Section: Discussionmentioning
confidence: 84%
“…The underlying assumption was that HIV-infected women may have worse access to or demand for contraception than HIV negative women, potentially due to barriers accessing and/or utilizing family planning services or fear of stigma from providers. [41], [42], [43] Overall, we found that approximately half of women with unintended births were actively trying to avoid pregnancy and presumably experienced contraceptive failure. Furthermore, in our adjusted model, there was no association between self-reported HIV status and contraception use, suggesting that, in Zimbabwe, the challenges to obtaining effective contraception apply equally to both HIV-uninfected and HIV-infected women, regardless of when they learned their serostatus.…”
Section: Discussionmentioning
confidence: 84%
“…Patient-provider interactions, attitudes of sexual partners, and cultural norms may further influence fertility desires. Qualitative research shows that HIV positive women rarely talk to service providers about their fertility desires and providers often have negative views of pregnancy among HIV-infected individuals; therefore, women are less likely to desire a child if their service provider disapproves or stigmatizes them [12, 23-24, 30-31]. It may be important that service providers interacting with women during ART initiation or PMTCT services are trained in providing empathetic care and offering family planning counseling to all women.…”
Section: Discussionmentioning
confidence: 99%
“…3240 Unfortunately, studies indicate that providers have not received training on how to provide safer pregnancy counselling, 40 and some have unsupportive attitudes toward fertility desires in HIV-positive patients. 151941 …”
Section: Discussionmentioning
confidence: 99%